Google Classroom Application: Use and Obstacles in Learning at SMA Negeri 1 Comal - Fauziyah, Riska; Riskiana; M. Sugeng Sholehuddin; Hendri Hermawan Adinugraha (LogicLink, 2024)
This research aims to use the Google Classroom application to learn Istomlearnious Education for class 1 Comal Pemalang Regency. This research uses a qualitative approach. This research uses a type of field research. The primary data sources for this research are Islamic Religious Education Teachers and Class X MIPA 4 Students at SMA Negeri 1 Comal. Secondary data sources in this research are documentation, official archives, books, journals, and other sources related to the title of this research. Data collection techniques in this research are observation, interviews, and documentation. Data analysis in this research uses qualitative data analysis, using an inductive qualitative descriptive method and the Miles Huberman method. The results of this research conclude that using the Google Classroom application in learning Islamic religious education for class X MIPA 4 at SMA Negeri 1 Comal is beneficial in online learning. This research using the Google Classroom application shows that teachers can monitor student learning activities, such as absences, material explanations, and assignment delivery. Supporting factors in implementing learning using Google Classroom are the teacher's readiness to deliver lessons, the teacher's delivery of material well, and adequate infrastructure at SMA Negeri 1 Comal. The inhibiting factor is the problem of a weak internet network for students on the coast or in places far from internet network towers.